Manajemen Strategi Pengembangan Pendidikan Non Formal - Puspito, Gaguk Wahyu; Swandari, Tatik; Rokhman, Mauhibur (Program S3 Pendidikan Islam Institut Pesantren KH. Abdul Chalim Pacet Mojokerto, 2021)
The research method used in this research is qualitative with a case study approach. Data collection in this study was carried out by means of observation, a document study, in-depth interviews, and data triangulation. The results of this study indicate that the Non-Formal Education of PKBM Wana Bhakti, Ngasem District, Bojonegoro Regency has successfully implemented a development strategy. The development strategy is carried out on the development of financing, facilities, and infrastructure, as well as the quality of graduates and student achievement. The results of the SPACE analysis result in the position of Strengths Opportunities (aggressive strategy), namely a strategy to take advantage of opportunities by using the strengths of educational institutions. The results of the SWOT analysis that produce alternative strategies are (a) developing Promotional Socialization and MoU of Fostered Villages, (b) developing Institutional infrastructure by accessing educational assistance from both central and local governments (c) developing skills so that it becomes a life skills-based educational institution. While the results of research on the implementation of the stages according to the theory of Pearce and Robinson, and Fred David. Evaluation and supervision are carried out by examining the basis of the strategy, comparing the expected results with actual results, taking corrective actions through supervision, regular meetings, and making reports.